2022
DOI: 10.1177/23259671221098989
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dynamic Postural Stability After ACL Reconstruction: Results Over 2 Years of Follow-up

Abstract: Background: The anterior cruciate ligament (ACL) is crucial for knee proprioception and postural stability. While ACL reconstruction (ACLR) and rehabilitation improve postural stability, the timing in improvement of dynamic postural stability after ACLR remains relatively unknown. Purpose: To evaluate changes in dynamic postural stability after ACLR out to 24 months postoperatively. Study Design: Case series; Level of evidence, 4. Methods: Patients undergoing ACLR were prospectively enrolled, and dynamic postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…[43][44][45] The presence of kinesiophobia thus may promote avoidance of complex biomechanical movements as a means of protecting the knee from further injury. [55][56][57] Brophy et al 33 observed that following ACLR in 42 patients, continued improvement in translational planes of motion was appreciated out to 24 months following surgery, while there remained largely no significant improvement in dynamic stability in rotational planes of motion at 24 months when compared with preoperative values. As such, rehabilitation should be directed at improving muscular strength and coordination in both translational and rotational planes of motion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[43][44][45] The presence of kinesiophobia thus may promote avoidance of complex biomechanical movements as a means of protecting the knee from further injury. [55][56][57] Brophy et al 33 observed that following ACLR in 42 patients, continued improvement in translational planes of motion was appreciated out to 24 months following surgery, while there remained largely no significant improvement in dynamic stability in rotational planes of motion at 24 months when compared with preoperative values. As such, rehabilitation should be directed at improving muscular strength and coordination in both translational and rotational planes of motion.…”
Section: Discussionmentioning
confidence: 99%
“…These included 3 translational plane assessments (medial/lateral [ML], anterior/posterior [AP], up/down [UD]) and 3 rotational plane assessments of the pelvis (left/right [LR], flexion/extension [FE], and internal/external rotation [Rot]). 33 Two additional 7 sessions of DMA testing following surgery were performed at 6-and 12 months postoperatively.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations